Extracellular Vesicles: Novel Roles in Neurological Disorders - Jin, Qian (Stem Cells Int, 2021)
Exosomes are small extracellular vesicles (EVs) secreted by almost all cells, which have been recognized as a novel platform for intercellular communication in the central nervous system (CNS). Exosomes are capable of transferring proteins, nucleic acids, lipids, and metabolites between neurons and glial cells, contributing to CNS development and maintenance of homeostasis. Evidence shows that exosomes originating from CNS cells act as suppressors or promoters in the initiation and progression of neurological disorders. Moreover, these exosomes have been shown to transfer molecules associated with diseases through the blood-brain barrier (BBB) and thus can be detected in blood. This unique feature enables exosomes to act as potential diagnostic biomarkers for neurological disorders. In addition, a substantial number of researches have indicated that exosomes derived from mesenchymal stem cells (MSCs) have repair effects on neurological disorders. Herein, we briefly introduce the roles of exosomes under physiological and pathological conditions. In particular, novel roles of exosomes as potential diagnostic biomarkers and therapeutic tools for neurological disorders are highlighted.